(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To explore the effect of aromatase inhibitors in the treatment of endometrial hyperplasia in post menopausal women. Materials and Methods: This observational longitudinal study was undertaken in 21 postmenopausal women diagnosed as having endometrial hyperplasia in a private clinic in Dhaka between July, 2009 to January 2014. Initially hyperplasia was diagnosed by thickened endometrium by ultrasound and confirmed by histopathologic examination of fractional curretage. Among the patients, 7 had complex hyperplasia without atypia; 14 had simple hyperplasia without atypia. All the patients were treated with letrozole 2.5 mg per day for 12 months and were monitored by transvaginal ultrasonogram every 3 months, subsequently followed up by history and transvaginal ultrasonogram 6 monthly for another 12 months. Main outcome measure was reduction of endometrial thickness. Informed written consent was obtained before enrollment in the study. Results: Mean endometrial thickness decreased by 81.66% following 12 months of treatment and the endometrial thickness was not increased in next 12 months follow up period. All patients were symptom free during this treatment. Conclusion: The results of this study indicate that treatment of endometrial hyperplasia with aromatase inhibitors can reduce endometrial thickness. So, aromatase inhibitors deserve attention for the conservative treatment of endometrial hyperplasia. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 78-82